Antibacterial Activity Test of Ethanol Extract from Jackfruit Leaves (Artocarpus heterophyllus) on Escherichia coli Bacterial Growth - Sri Marfuati*; Mustika Weni (Universitas Syiah Kuala, 2023)
Infectious diseases continues to grow in the health sector due to the colonization of infectious organisms and is the main cause of death worldwide. Infection can be caused by bacteria, fungi, viruses and parasites. One example of bacteria that can cause infection is Escherichia coli. Jackfruit (Artocarpus heterophyllus) have been used by communities for to treat or handle various diseases. This study aims to determine the antibacterial activity from ethanol Jackfruit Leaves against the growth inhibition of the bacterium Escherichia coli using three concentrations of 12,5%, 25% and 50%. Extraction was done by maceration method using ethanol 96%. Antibacterial activity test was performing using the well diffusion method. This results of this study indicate that ethanol extracts of Jackfruit leaves are considered as antibacterial and have antibacterial strength against Escherichia coli at concentrations of 50% include strong groups to inhibit Escherichia coli, while at a concentration of 12,5% and 25% include medium groups to inhibit Escherichia coli.